A novel sucrose hydrolase from the bombycoid silkworms Bombyx mori, Trilocha varians, and Samia cynthia ricini with a substrate specificity for sucrose. (June 2015) - Wang, Huabing; Kiuchi, Takashi; Katsuma, Susumu; Shimada, Toru
Abstract: Although membrane-associated sucrase activity has been detected in the midgut of various lepidopteran species, it has not yet been identified and characterized at the molecular level. In the present study, we identified a novel sucrose hydrolase (SUH) gene from the following three bombycoid silkworms: Bombyx mori, Trilocha varians, and Samia cynthia ricini and named them BmSuh, TvSuh, and ScSuh, respectively. The EST dataset showed that BmSuh is one of the major glycoside hydrolase genes in the larval midgut of B. mori . These genes were almost exclusively expressed in the larval midgut in all three species, mainly at the feeding stage. SUHs are classified into the glycoside hydrolase family 13 and show significant homology to insect maltases. Enzymatic assays revealed that recombinant SUHs were distinct from conventional maltases and exhibited substrate specificity for sucrose. The recombinant BmSUH was less sensitive to sugar-mimic alkaloids than TvSUH and ScSUH, which may explain the reason why the sucrase activity in the B. mori midgut was less affected by the sugar-mimic alkaloids derived from mulberry. Graphical abstract: Highlights: We identified a novel gene encoding sucrose hydrolase (SUH) from each of three bombycoid silkworms. Suh is expressed specifically and abundantly in larval midgut of each species. SUHs show remarkable substrate specificity for sucrose. This property is distinct from other α-glucosidases in insects. Bombyx mori SUH is more resistant to the sugar-mimic alkaloids in mulberry than those of the other two non-mulberry feeders.